2008
DOI: 10.1016/j.jns.2007.12.034
|View full text |Cite
|
Sign up to set email alerts
|

Akt1 gene deletion and stroke

Abstract: Activation of Akt has been implicated as a major contributor to neuronal survival after an ischemic insult. Numerous neuroprotective agents have been shown to augment Akt activity, suggesting that this protein represents a major mechanism of cellular salvage after injury. Estrogen is known to augment Akt, but the possibility that Akt plays a differential role in the male and female brain has yet to be evaluated. In this study, we employed both pharmacological and genetic approaches to investigate the role of A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 35 publications
1
15
0
Order By: Relevance
“…No differences were seen in physiological parameters (Table S4) or blood flow (Table S5) in female mice treated with vehicle or embelin. We have previously shown that no sex differences exist in physiological parameters or blood flow in our model (39).…”
Section: Resultsmentioning
confidence: 57%
“…No differences were seen in physiological parameters (Table S4) or blood flow (Table S5) in female mice treated with vehicle or embelin. We have previously shown that no sex differences exist in physiological parameters or blood flow in our model (39).…”
Section: Resultsmentioning
confidence: 57%
“…In this study, mice treated with compound C demonstrated no additional neuroprotective effects with IPC, suggesting that AMPK inhibition is the common neuroprotective pathway. Although a floor effect is possible, this is less likely as mice treated with combination therapy still had substantial infarcts (30%), and we have shown previously that infarct volumes can be reduced to as low as 16% with other neuroprotective agents in earlier studies using this MCAO model (Li et al, 2008). However, it does remain possible that the smaller infarcts are masking an additive effect of AMPK and IPC.…”
Section: Discussionmentioning
confidence: 96%
“…Neuronal-specific transgenic mice overexpressing an activated form of Akt after injury showed reduced infarct area after middle cerebral artery occlusion (MCAO), 6 but it is not clear whether these levels of expression and activity of Akt are physiologic. Indeed mice deficient in Akt1, a major contributor to neuronal survival, do not show differences in stroke outcome 8 but the observation that Akt1-deficient mice and control mice have equivalent levels of phosphorylated Akt suggests that alternate isoforms of Akt compensate for germline loss of Akt1. 8 Recent studies revealed that increasing Akt activity by removal of its endogenous inhibitor, carboxyl terminal modulator protein (CTMP), protects neurons from ischemia-induced death.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed mice deficient in Akt1, a major contributor to neuronal survival, do not show differences in stroke outcome 8 but the observation that Akt1-deficient mice and control mice have equivalent levels of phosphorylated Akt suggests that alternate isoforms of Akt compensate for germline loss of Akt1. 8 Recent studies revealed that increasing Akt activity by removal of its endogenous inhibitor, carboxyl terminal modulator protein (CTMP), protects neurons from ischemia-induced death. 9 This provides encouraging evidence that increasing endogenous activation of all Akt isoforms are protective, although how CTMP affects Akt activity has not been clearly defined.…”
Section: Introductionmentioning
confidence: 99%